The simple path to wealth : your road map to financial independence and a rich, free life - Collins, J. L. (Blogger) (Authors Equity, 2025)
"This comprehensive guide covers everything from debt elimination to optimizing retirement accounts, all while exposing the marketing myths and investment industry practices that keep most people from building real wealth. Collins shares specific, actionable strategies for both wealth-building and wealth-preservation phases, with a straightforward approach to asset allocation that anyone can implement"--